Penerapan Metode Role Playing dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Akidah Akhlak di Madrasah Tsanawiyah Al-Khairat Nunukan - Husnul Ilmiah (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2025)
Education is a very important human right in life, because it plays a role in developing the potential of individuals as a whole. This study aims to evaluate the application of the Role Playing method in improving students' understanding of the subject of Moral Beliefs at Madrasah Tsanawiyah Al-Khairaat Nunukan. This study uses a Classroom Action Research (PTK) approach with a qualitative method that focuses on data collection through observation, interviews, and documentation. This research was carried out in two cycles, with 20 research subjects consisting of 10 female students and 10 male students. The results of the study showed that in the pre-cycle, students experienced limitations in understanding the material due to the use of monotonous lecture methods. In cycle I, even though the Role Playing method has been applied, there are still obstacles in student involvement. However, in cycle II, with improvement and more motivation, student activities and learning outcomes increased significantly, with 95% of students achieving learning completion. This study proves that the Role Playing method is effective in increasing students' understanding, motivation, and involvement in learning Akidah Akhlak. Based on these results, it is recommended that the Role Playing method continue to be used to improve the quality of learning.